Hungarian Monitoring, 21 August 1989 . [Magyar rádiófigyelő], 1989. augusztus 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Reports on Prague demonstrations where four Hungarian members of Alliance of Young Democrats (Fidesz) arrested - Statements and guesses from Warsaw on the new government - Bonn's opinions on processes in Eastern Europe - Who was shot and why on West-East German border? - Power struggle in Beijing for military leadership posts Domestic Affairs: - Reactions to Miklós Németh's speech in Cegléd - The Csaba Tabajdi case - Pan-European picnic: GDR citizens escape into Austria - Conversation with a Alliance of Young Democrats (Fidesz) member denied entry to Czechoslovakia by Czechoslovak border guards for not having valid travel permit Economy: - Meeting of scientists and businesspeople of Hungarian origin Külpolitika: - Tudósítások a prágai tüntetésről, ahol négy magyar FIDESZ-est is letartóztattak - Varsói jelentések és találgatások az új kormányról - Bonni vélemények a kelet-európai folyamatokról - Kik és miért lövöldöztek az NSZK-NDK határon? - Hatalmi harc Pekingben a katonai vezetői posztok körül Belpolitika: - Németh Miklós ceglédi beszédének visszhangja - Tabajdi Csaba ügye - Páneurópai piknik - NDK állampolgárok Ausztriába szökése - Beszélgetés egy Fidesz taggal, akit a csehszlovák határőrök érvényes úti okmány ellenére nem engedtek be Csehszlovákiába Gazdaság: - Magyar származású tudósok és üzletemberek találkozója